Consumer complaint behavior in telecommunications: The case of mobile phone users in Spain - Teresa Garín-Mu\~noz; Covadonga Gijón; Teodosio Pérez-Amaral; Rafael López (International Telecommunications Society (ITS), 2014)
This work analyzes the post-purchase behavior of mobile phone users once they have experienced a service failure. Taking into account the existing literature on Consumer Complaint Behavior (CCB), a survey for 4249 individuals in Spain is used for specifying econometric equations explaining the determinants of the complaining decision and the impact of a proper management of complaints on overall satisfaction. The results suggest that dissatisfaction is not a necessary condition for complaining and that the propensity to complain is different depending on the type of problem experienced by the customer. Another relevant finding of this study is that a good handling of complaints by the company may constitute a source of improvement in the overall user satisfaction and profitabity of the firm. This result is of great interest for its implications when designing the marketing strategy of companies. Accordingly it seems reasonable to use the complaint management as a powerful tool to retain customers.
Keywords: 330; Consumer Complaint Behavior; Mobile phones; Consumer Retention; Consumer Satisfaction Consumer Loyalty; Voice; Exit; Service Failure; Complainers